School Dropout in the Indonesia-Timor Leste Border: Moderating Role of Social Environment and Learning Motivation - Hernawati, Retno; Panie, Maria Yuliana; Neonufa, Samrid; Tajuddin, Al Ihzan (Lectura : Jurnal Pendidikan, 2025)
This study is motivated by persistently high dropout rate at senior high school level in the border region between Indonesia and Timor-Leste. The school participation rate at this level reaches only 60.42%, indicating that 39.58% of students do not continue or complete their education. The purpose of this study is to examine the influence of family environment and peer on the tendency to drop out of school, as well as to evaluate the moderating role of learning motivation in these relationships. This research employed a quantitative approach using an explanatory survey method. The study population included all high school dropouts across 12 sub-districts in Malaka Regency. A proportional sampling technique was applied, resulting in a total sample of 180 dropout students. Data were collected using a questionnaire with a five-point Likert scale. The data were analyzed using multiple regression analysis and Moderated Regression Analysis (MRA) with the assistance of SPSS version 27. The results of the study showed that the family environment and peer have a significant negative effect on school dropout. Learning motivation significant moderates, the relationship between the family environment, peers and school dropout. In conclusion, both the family environment and peer groups significantly influence school dropout rates in border areas, while learning motivation serves as a protective factor that can mitigate these effects. Therefore, efforts to enhance students’ learning motivation may be an effective strategy to reduce dropout rates in such regions.